Innovative Business Models in the Pharmaceutical Industry: A Case on Exploiting Value Networks to Stay Competitive. (6th November 2014) - Capo, Francesca; Brunetta, Federica; Boccardelli, Paolo
The search to find a more efficient and effective way of managing processes, while maintaining the integrity of research and manufacturing activities, has led pharmaceutical firms, and other actors of the renewed pharmaceutical supply chain, to modify their own business models. This article aims to emphasize this dimension, highlighting, via the observation of a network of firms operating at different stages of the pharmaceutical supply chain, how business models have succeeded in complementing each other and in originating a value creation network.